Assessing infant sleep practices and other risk factors of SIDS in Zambia: a cross-sectional survey of mothers in Lusaka, Zambia - Godwin K. Osei-Poku; Lawrence Mwananyanda; Patricia A. Elliot; William B. MacLeod; Somwe Wa Somwe; Rachel C. Pieciak; Christopher J. Gill (BMC, 2022)
Abstract Background Having infants sleep with their parents and sleeping face down or on their sides are the two most proximate and modifiable risk factors for sudden infant death syndrome (SIDS). Little is known about the burden of SIDS or the prevalence of these risk factors in Africa. Our primary objective was to determine the prevalence of modifiable risk factors of SIDS in Lusaka, Zambia. Methods We conducted cross-sectional surveys with recent mothers of infants aged < 1 year across two busy urban clinic sites in Lusaka, Zambia. We used log-binomial regression analysis to identify factors predictive of bedsharing and prone sleeping. Results Surveys were conducted with 478 mothers between April-May 2021. The sleep-related risk factors, bedsharing and side sleeping, were widely prevalent. 89.5% of respondents indicated that they share a bed with the infant during sleep, 73.0% preferred putting their baby on its side, and 19.9% preferred the prone position. Only 6.7% of respondents described using the safer, supine position. Age of infant was the only factor which was predictive of prone sleeping. Infants > 2 months old were twice as likely to be put to sleep in a prone position compared to infants aged less than 2 months old. Mothers reported that they rarely (24.1%) received advice from medical caregivers to use the supine position. Maternal use of alcohol (12.0%) and tobacco (0.8%) during pregnancy were uncommon. Conclusions Bedsharing and placing the infant to sleep on the side were commonly reported among the mothers we interviewed. Whether this represents an opportunity to reduce SIDS in Zambia is unclear since accurate data on the burden of SIDS in Zambia is not available. There is a need for increased awareness of SIDS and more prospective data collection on its burden and related risk factors in these African populations.